Bullying - Yahaya, Azizi (2004)
Abstracts: In recent years, there’s been much discussion about bullying issues surrounding children as well as adults. The issue is alarming to say the least and gives us, as parents, cause for concern. Bullying is when someone keeps doing or saying things to have power over another person. Bullying can take many forms like physical, emotional, verbal, psychological and combination of these. Some bullies may not even understand how wrong their behavior is and how it makes the person being bullied feel. A lot of reasons why people bully is that, they may see is as a way of being popular, or making themselves look tough and in charge. Some bullies do it to get attention or things, or to make people afraid and might be jealous of the person they are bullying. There are four kinds of bullies, it is physical bullies, verbal bullies, relational bullies and reactive victims. Many factor causes of bullying, like parental relationship, school failure and peer rejection. Suggestion are meant to provide a beginning for attacking the behavior of child bullying, not the child. Determine the seriousness of the behavior, looks for triggers to the behavior, determine if the child is mimicing abuse and educate the child about acceptable social behaviors are the recommended ways to remediate bullying. People including students, parents, teachers and administrators can make a significant difference to the lives of all the bullies.